Patterns of network trade: A comparison between East Asia and European union - Son Thanh Nguyen (Elsevier, 2021)
The production networks in East Asia and European Union are characterized by large shares of trade in intermediate goods or network trade between countries within each region. However the pattern of network trade in the two regions could be very different due to regional variations in sociocultural, political, historical and institutional factors. This paper investigates and compares the pattern of network trade in East Asia and European Union. It confirms that, while network trade shows a “hub-and-spoke pattern” in European Union, it is more like a “network pattern” in East Asia.